EFEK PEMANASAN TERHADAP TOTAL ANTIOKSIDAN DARI BEBERAPA JENIS SAYURAN TINUTUAN - Momuat, Lidya Irma (Sam Ratulangi University, 2010)
ABSTRACTMomuat et al., 2010. Heating effect on total antioxidant of some Tinutuan vegetables.A research was done to to study the effect of heating on total antioxidant some tinutuan vegetables. Total antioxidant of some vegetables was evaluated using ferric reducing antioxidant plasma method. The results show that vegetables treat by heating possessed high antioxidant activity. Total antioxidant of unheating gedi, spinach, kangkung and kemangi were 0.36, 1.84, 0.30 and 0.58, respectively. Total antioxidant of heating gedi, spinach, kangkung and kemangi were 0.93, 2.74, 0.69 and 1.07, respectively. High total antioxidant activity of heating vegetables caused by its antioxidant compound increase after heating time.Keywords : heating, vegetables, tinutuan, total antioxidant